2019
DOI: 10.3389/fonc.2019.00093
|View full text |Cite
|
Sign up to set email alerts
|

Putative Role of Circulating Human Papillomavirus DNA in the Development of Primary Squamous Cell Carcinoma of the Middle Rectum: A Case Report

Abstract: Here we present the case of a patient affected by rectal squamous cell carcinoma in which we demonstrated the presence of Human Papillomavirus (HPV) by a variety of techniques. Collectively, the virus was detected not only in the tumor but also in some regional lymph nodes and in non-neoplastic mucosa of the upper tract of large bowel. By contrast, it was not identifiable in its common sites of entry, namely oral and ano-genital region. We also found HPV DNA in the plasma-derived exosome. Next, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…At this regard, some authors reported circulating HPV DNA in the serum of patients with HPV-associated invasive cancer (10) and as marker for disease extent and recurrence (14). We also found HPV DNA in the serum derived-extracellular vesicles (EVs) of breast pathologies affected women as well as in patient with HPV DNA positive squamous cell carcinoma of the middle rectum (15, 16). EVs are a heterogeneous population of vesicles, which includes exosomes, microvesicles, and apoptotic bodies that differ in size and biophysical properties (17).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…At this regard, some authors reported circulating HPV DNA in the serum of patients with HPV-associated invasive cancer (10) and as marker for disease extent and recurrence (14). We also found HPV DNA in the serum derived-extracellular vesicles (EVs) of breast pathologies affected women as well as in patient with HPV DNA positive squamous cell carcinoma of the middle rectum (15, 16). EVs are a heterogeneous population of vesicles, which includes exosomes, microvesicles, and apoptotic bodies that differ in size and biophysical properties (17).…”
Section: Introductionmentioning
confidence: 75%
“…We previously demonstrated that circulating HPV DNA can be found in serum derived-extracellular vesicles (EVs) in women with breast pathologies as well as in patient with HPV DNA positive squamous cell carcinoma of the middle rectum (15, 16). Here, as described in the first part of the study approved by the local ethics committee (145/2015/U/Sper), we enrolled 59 BC affected-patients and we searched for the presence of HPV DNA in the serum derived-EVs.…”
Section: Resultsmentioning
confidence: 99%
“…There are some evidence demonstrating that HPV DNA in exosomes participated in the process of cancer. HPV DNA in plasma-derived exosomes was detected in rectal squamous cell carcinoma patients (Ambrosio et al, 2019). Ambrosio et al isolated exosomes from the HPV DNA-positive cell line CaSki, which can transfer DNA to normal cell lines.…”
Section: Dnamentioning
confidence: 99%
“…While there is a clear association of anal SCC with the most common subclasses of high risk HPVs, including types 16, 18, 31, and 33, a correlation to rectal SCC has not been clearly established yet [16,17]. One possible explanation for HPV-associated SCC in the rectum is circulating HPV DNA as discussed by Ambrosio et al [8]. An alternative pathogenetic pathway may be a misplacement of HPV-infected neoplastic epithelial cells from the anal canal with subsequent implantation of these tumor cells into the rectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the higher rectum there is no clear evidence for an association with HPV infections but an association with human immunodeficiency virus (HIV) [5][6][7]. One possible explanation of HPV infection in the higher rectum is circulating HPV deoxiribonucleic acid (DNA) [8]. Anal SCC affects more women than men and typically appears in the sixth decade of life, mostly with pelvic pain and bleeding [4,9,10].…”
Section: Introductionmentioning
confidence: 99%